Diagnosis and Management of Ventricular Septal Defects - P. Syamasundar Rao (Reviews in Cardiovascular Medicine)
This review addresses the diagnosis and management of ventricular septal defects (VSDs). The VSDs are classified on the basis of their size, their number, and their location in the ventricular septum. Natural history of VSDs includes spontaneous closure, development of pulmonary hypertension, onset of infundibular obstruction, and progression to aortic insufficiency. While initial diagnostic approaches such as careful history-taking, physical examination, chest X-rays, and electrocardiograms provide basic information, echo-Doppler studies are essential for assessing the defect's clinical significance and determining the need for intervention. Intervention is usually indicated for symptomatic patients with moderate- to large-sized VSDs. Surgical closure is advised for perimembranous, supracristal and inlet VSDs, and for deficits involving prolapsed aortic valve leaflets. While percutaneous methods to occlude perimembranous VSDs with Amplatzer Membranous VSD Occluder are feasible, they are not recommended due to a notable risk of inducing complete heart block in a significant number of patients. Alternatively, percutaneous and hybrid methods employing the Amplatzer Muscular VSD Occluder are effective for treating large muscular VSDs. The majority of treatment options have demonstrated satisfactory outcomes. However, practitioners are urged to exercise caution in managing small defects to avoid unnecessary procedures and to ensure timely intervention for large VSDs to prevent pulmonary vascular obstructive disease.